Mapping global media and communication strategies in adolescent reproductive health promotion: A scoping review - Najma Afifa; Zahroh Shaluhiyah; Ratih Indraswari (Journal of Public Health and Development, 2026)
Mercury presents a significant environmental health hazard due to its ability to bioaccumulate in the food chain, posing risks through the consumption of contaminated fish. This systematic review aims to analyze and compare mercury levels in human populations, specifically focusing on the health risks associated with fish consumption in urban versus rural areas. The review followed PRISMA guidelines and included articles published between January 1, 2020 and March 15, 2025 from PubMed, Scopus, and ScienceDirect. A total of 768 articles were identified, and seven studies met the inclusion criteria. Data extraction was performed, and study quality was assessed using the JBI checklist and risk of bias assessment with ROBINS-E. Data were extracted and synthesized using RevMan 5.4 for the meta-analysis. The meta-analysis showed substantially higher mercury levels in rural populations (SMD 2.76; 95% CI: 2.63–2.89), largely influenced by dietary patterns, predominant fish species, and environmental contamination levels. Health effects associated with elevated mercury exposure included neurodevelopmental risks, elevated mercury levels in pregnant women, and increased vulnerability among populations with high reliance on freshwater fish. These findings highlight the need for targeted public health strategies to mitigate mercury exposure while maintaining the nutritional benefits of fish consumption.